Effect of Security on Hostels’ Price Premiums: a hedonic pricing approach - Cró, Susana (2020)
This article evaluates the impact of security in the hostel industry on the willingness to pay by customers. More specifically, given the importance of security in the decision to travel and in the choice of a given destination, we analyze the impact of security guest reviews on a consumer-generated website on hostel room prices. Furthermore, we investigate whether the impact of security guest reviews on the hostel room prices is higher for the hostels located in the countries with the lowest ranking in the Global Peace Index. Finally, we examine whether females and older guests are willing to pay a premium in terms of price for a hostel with a higher level of security. For this purpose, we estimate a hedonic price function for a sample of consumer reviews of 477 hostels in 22 worldwide capitals, with different levels of peace, from Hostelworld. The results highlight the importance of security on the determination of hostel room prices. We find that customers are willing to pay a higher premium in terms of price, in the least worldwide peaceful countries, for a hostel room with higher levels of security. In the case of women and older guests, the premium they are willing to pay is higher.